Comparing knowledge and attitudes to dementia care in Brazilian and UK GPs to guide future decisions about educational interventions. Issue 2 (2nd April 2020) - Jacinto, Alessandro Ferrari; Gordon, Adam Lee; Samra, Rajvinder; Steiner, Ana Beatriz; Mayoral, Vania Ferreira de Sá; Citero, Vanessa de Albuquerque
ABSTRACT: Background : Dementia training for Brazilian general practitioners (GPs) is underdeveloped. We investigated knowledge and attitudes to dementia management among Brazilian GPs and compared these with previous UK findings to inform future decisions about how training is structured. Methods : A total of 115 Brazilian GPs were asked to complete a Portuguese translation of a questionnaire previously used in the UK. This comprised a 14-item multiple-choice knowledge quiz, and a 5-point Likert-scale questionnaire assessing attitudes across 10 dementia management domains. Exploratory factorial analysis was conducted for attitudes. Results : Attitudes toward dementia demonstrated the same underlying factor structure, "heartsink" and "heartfelt" factors, in Brazil as in previous UK studies, explaining 61.6% of variance in responses. Knowledge scores were negatively correlated with heartfelt and heartsink factors. Conclusions : Greater knowledge about dementia was associated with some pessimism about dementia care. The similarity in the structure of attitudes toward dementia management between Brazilian and UK GPs provides a starting point for shared educational approaches targeting attitudes.